Mathematical model of a shim valve of a monotube shock absorber / Vienvamzdžio amortizatoriaus plokštelinio vožtuvo matematinis modelis - Paulius Skačkauskas; Vaidas Vadluga; Vidas Žuraulis (Mokslas: Lietuvos Ateitis, 2016)
In the work, a mathematical model of a shim valve, used in monotube shock absorbers, designed to determine the deformations of the shims which form during the exploitation of the shock absorbers, is presented. The characteristic of the damping force formed by the shock absorber depends on the deformations. In the designed model, the amount, geometric dimensions, arrangement and the material properties of the shims are evaluated, and the contact forces, which form between the shims, are determined. The described model of the shim valve is presented in the environment of the software package MATLAB/Simulink, the analysis of the designed model is done using the software package ANSYS 15.0.